To Assess the Effect of Early Ambulation and Progressive Exercise on Post-cesarean Section Recovery among Women at Selected Hospitals of the City - Vilas Jadhav, Charushila; Gosavi, Amarja (International Journal of Nursing Research, 2023)
Introduction: Cesarean section is a life-saving procedure firmly ensconced in obstetric practice. It poses a barrier to breast-feeding initiation related to delay in maternal-infant contact, maternal pain, and exhaustion. Early ambulation reduces the post-operative complications such as atelectasis, GI discomfort, and circulatory problems. Methodology: A quasi-experimental research design was used for this study carried out in postnatal wards of selected hospitals of the city. The study samples comprised 110 post-cesarean mothers divided into 55 in the experimental and 55 in control group using non-probability purposive sampling technique. Data were collected based on demographic variables, and assessing the post-operative recovery of mothers after the interventions (i.e., early ambulation and progressive exercise) to them through structured nursing assessment sheet. The data were analyzed using descriptive and inferential statistics such as standard deviation, Karl Pearson’s correlation, Unpaired t-test, and Chi-square test. Results: The analysis findings depict that the corresponding P < 0.05. After intervention of early ambulation and progressive exercise given to mothers in the experimental group, it depicted that majority of the samples 41 (74.55%) had excellent outcome, 14 (25.45%) had good outcome, whereas in control group, 36 (65.45%) had good outcome, and 19 (34.54%) had poor outcome. Conclusion: Above data show that early ambulation and progressive exercises among experimental group were effective and improve postoperative recovery early as compared to control group.